Cross-linked polyether-based solid electrolyte and photo-initiation preparation method and application thereof

By initiating the polymerization of cyclic ether monomers with ultraviolet light, and combining crosslinking agents and auxiliaries, the problem of the single synthesis route and control difficulties of polyether-based solid electrolytes has been solved, thereby improving the performance of solid electrolytes and the application potential of lithium metal batteries.

CN119315124APending Publication Date: 2025-01-14CENT SOUTH UNIV

Patent Information

Application Number
CN202411484912.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing polyether-based solid electrolytes have a single synthetic route, and the polymerization process is difficult to control, resulting in inconsistent material properties and difficulties in large-scale production. Furthermore, traditional Lewis acid initiators are sensitive to the environment.

Method used

By employing ultraviolet light initiation technology, the polymerization of cyclic ether monomers is initiated through the synergistic effect of crosslinking agent, auxiliary agent I, and auxiliary agent II, thereby optimizing polymerization behavior and uniformity and improving the stability and conductivity of solid electrolytes.

Benefits of technology

Precise control of the polymerization process was achieved, which improved the ionic conductivity and electrochemical performance of the solid electrolyte, and enhanced the safety and cycle stability of lithium metal batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315124A_ABST
    Figure CN119315124A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of solid electrolytes, and particularly relates to a preparation method of a cross-linked polyether-based solid electrolyte, which comprises the following steps: polymerizing a precursor solution containing an ether monomer, a cross-linking agent containing an epoxy group, an electrolyte salt, an auxiliary agent I and an auxiliary agent II under ultraviolet irradiation to obtain the cross-linked polyether-based solid electrolyte, the auxiliary agent I is a compound which contains a structure shown in a formula 1 # imgabs0 # and can release free radicals under ultraviolet light; the auxiliary agent II is at least one cationic organic matter of diazonium salt, iodonium salt, sulfonium salt, ferrocene salt, sulfonyloxy ketone and triaryl siloxy ether. The invention also discloses the material prepared by the preparation method and an application of the material in a battery. According to the invention, the cyclic ether monomer, the cross-linking agent, the assistant I and the assistant II are polymerized under ultraviolet light, so that the polymerization of the cyclic ether monomer can be realized based on a brand new photo-initiation mechanism, and furthermore, the polymerization behavior and uniformity can be optimized, so that the comprehensive properties such as stability, mechanical property, conductivity and the like of the prepared solid electrolyte are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of battery materials, and in particular relates to the field of solid electrolytes. Background Art

[0002] With the rapid development of electric vehicle revolution and portable electronic devices, the market demand for high energy density and high safety energy storage systems is becoming increasingly urgent. Metallic lithium has a low redox potential (-3.04V, relative to standard hydrogen electrode) and a high theoretical specific capacity (3860mAh g -1 ), is considered to be the key negative electrode material for improving the energy density of lithium batteries. However, the high activity of lithium metal negative electrodes leads to severe challenges such as rapid consumption of liquid electrolytes, non-uniform deposition of lithium ions, and uncontrolled growth of lithium dendrites, which seriously threaten the safety and cycle life of batteries.

[0003] To solve the above problems, solid electrolytes have emerged as a substitute for liquid electrolytes and are considered to be an effective way to solve the safety problems of lithium metal batteries. Solid electrolytes are mainly divided into two categories: inorganic solid electrolytes and polymer solid electrolytes. Among them, although inorganic solid electrolytes have high ionic conductivity and good mechanical strength, their inherent brittleness and high production costs limit their practical development and wide application. In contrast, polymer electrolytes show flexibility, easy processing and low cost, and have become the focus of research. In particular, polyether-based solid electrolytes (such as poly 1,3-dioxolane) based on the polymerization of cyclic ethers (such as 1,3-dioxolane) show great application potential due to their excellent lithium ion transmission ability, electrochemical stability and simple preparation process.

[0004] Currently, the synthesis route of polyether-based solid electrolytes is relatively simple, mainly relying on the ring-opening polymerization reaction promoted by Lewis acid initiators. This traditional method is not only sensitive to water and oxygen in the environment, but also faces challenges such as difficulty in accurately controlling the polymerization reaction, large fluctuations in polymerization time and degree of polymerization, which limits the consistency of material performance and large-scale production. Summary of the invention

[0005] In view of the problems that the existing polyether-based solid electrolyte polymerization method is single and the polymerization process is difficult to control, the first purpose of the present invention is to provide an improved preparation method of a cross-linked polyether-based solid electrolyte, aiming to optimize the polymerization behavior based on a new photoinitiator method, improve the polymerization uniformity, and improve the comprehensive performance of the material such as electrical conductivity, mechanical properties and stability.

[0006] The second object of the present invention is to provide a cross-linked polyether-based solid electrolyte prepared by the preparation method and its application in alkali metal secondary batteries.

[0007] The third object of the present invention is to provide an alkali metal secondary battery comprising the cross-linked polyether-based solid electrolyte and a preparation method thereof.

[0008] A method for preparing a cross-linked polyether-based solid electrolyte, comprising polymerizing a precursor solution containing an ether monomer, a cross-linking agent containing an epoxy group, an electrolyte salt, an auxiliary agent I and an auxiliary agent II under ultraviolet light irradiation to obtain a cross-linked polyether-based solid electrolyte;

[0009] The auxiliary agent I is a compound having a structure of formula 1 and capable of releasing free radicals under ultraviolet light; the auxiliary agent II is at least one cationic organic substance selected from diazonium salts, iodonium salts, sulfonium salts, ferrocenium salts, sulfonyloxy ketones, and triarylsiloxane ethers;

[0010]

[0011] The R1 is at least one of H, C1-C6 alkyl, C1-C6 alkoxy, cyano, fluorine, chlorine, bromine and iodine;

[0012] The R2 is an alkyl group, a phenyl group, or is cyclically linked to the α-position C of the benzene ring to form a ring; wherein the alkyl group, the phenyl group and the ring are allowed to have substituents, and the substituents include at least one of a C1-C6 alkyl group, a C1-C6 alkoxy group, a C1-C6 alkanoyl group, a phenyl group, a hydroxyl group, a phosphoryl group, a cyano group, a fluorine atom, a chlorine atom, a bromine atom and an iodine atom.

[0013] The present invention uses cyclic ether monomers and cross-linking agents, auxiliary agents I and auxiliary agents II to polymerize under ultraviolet light, so that the polymerization of cyclic ether monomers can be achieved based on a new photoinitiator mechanism. Not only that, the polymerization behavior and uniformity can also be optimized, thereby improving the comprehensive properties of the prepared solid electrolyte, such as stability, mechanical properties, and conductivity.

[0014] In the present invention, the auxiliary agent I is at least one of the compounds of formula 1-A, formula 1-B, formula 1-C, and formula 1-D;

[0015]

[0016]

[0017] The R3 to R6 mentioned above are independently H, C1 to C6 alkyl, hydroxyl, C1 to C6 alkoxy, C1 to C6 alkanoyl, phosphoryl, cyano, chlorine or bromine.

[0018] The X is O or S.

[0019] In the present invention, the auxiliary agent II is a compound containing organic cations of formula 2 to formula 5;

[0020]

[0021] The R7~R 12 The aromatic group alone contains at least one aromatic ring selected from benzene, naphthalene, anthracene, phenanthrene, and pyrene. In addition, the aromatic ring is allowed to carry a substituent, such as an alkyl group, an alkoxy group, a halogen group, and further can be at least one selected from phenyl, tolyl, cumene, naphthalene, anthracene, phenanthrene, pyrene, and derivatives thereof.

[0022] In the present invention, the anions in the auxiliary agent II include at least one of hexafluorophosphate anions, tetrafluoroborate anions, hexafluoroantimonate anions, hexafluoroarsenate anions, and trifluoromethanesulfonate anions.

[0023] In the present invention, the cross-linking agent containing epoxy groups comprises at least one of pentaerythritol glycidyl ether, trimethylolpropane triglycidyl ether, polyethylene glycol diglycidyl ether, glycerol diglycidyl ether, polypropylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, resorcinol diglycidyl ether, isocyanuric acid triglycidyl ester, glycidyl ether oxypropyl cage polyhedral silsesquioxane, and 1,3-bis(3-glycidyl ether oxypropyl)tetramethyldisiloxane.

[0024] In the present invention, the ether monomer is an unsaturated epoxy monomer; preferably a three- to six-membered cyclic ether and corresponding fluorine-substituted or carbon-chain-substituted product.

[0025] Further preferably, the ether monomer includes at least one of ethylene oxide, 3,4-epoxy-1-butene, 3,3,3-trifluoropropylene oxide, tetrahydrofuran, 2-methyltetrahydrofuran, 3,3,4,4,5,5-hexafluorotetrahydropyran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 4-(trifluoromethyl)-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2,2,4,4,5,5-hexamethyl-1,3-dioxolane, 1,3,5-trioxane, 2,2-dimethoxy-4-(trifluoromethyl)-1,3-dioxane, 1,3,5-trioxane, 1,3-dioxane, and 1,4-dioxane.

[0026] Preferably, the electrolyte salt comprises at least one of a conductive lithium salt, a conductive sodium salt, and a conductive potassium salt, and preferably comprises at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(oxalateborate), lithium bis(fluorooxalateborate), lithium difluorobis(oxalateborate), lithium difluorobis(oxalatephosphate), lithium difluorophosphate, lithium hexafluoroarsenate, sodium bis(trifluoromethanesulfonyl)imide, sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, sodium bis(fluorosulfonyl)imide, sodium bis(oxalateborate), sodium bis(fluorooxalateborate), sodium difluorobis(oxalatephosphate), sodium difluorophosphate, sodium hexafluoroarsenate, potassium bis((fluorosulfonyl)imide), potassium fluoroborate, potassium hexafluorophosphate, and potassium perchlorate.

[0027] In the precursor solution, the electrolyte salt concentration is 0.1-5 mol / L, the crosslinking agent content is 0.1-25 wt%, the auxiliary agent I content is 0.01-10 wt%, and the auxiliary agent Ⅰ content is 0.01-10 wt%. Further, the electrolyte salt concentration is 0.5-2 mol / L, the crosslinking agent content is 1-5 wt%, the auxiliary agent I content is 0.5-2 wt%, and the auxiliary agent Ⅰ content is 0.5-2 wt%. Further, the electrolyte salt concentration is 0.8-1.2 mol / L, the crosslinking agent content is 2-4 wt%, the auxiliary agent I content is 0.8-1.5 wt%, and the auxiliary agent Ⅰ content is 0.8-1.5 wt%.

[0028] The wavelength of the ultraviolet lamp is 100-420nm, and can further be 380-400nm, and the irradiation intensity is 20-200mW / cm;

[0029] Preferably, the polymerization time is 1 to 30 minutes, and further can be 2 to 5 minutes.

[0030] The present invention also provides a solid electrolyte membrane, which is obtained by the preparation method of the present invention.

[0031] In the present invention, the synergistic combination of the crosslinking agent, auxiliary agent I and auxiliary agent II induces the photoinitiated polymerization of the cyclic ether monomer, and can optimize the polymerization behavior, improve the polymerization uniformity and the physicochemical structure, and further improve the ionic conductivity, oxidation resistance, cycle stability and other properties.

[0032] The present invention also provides an alkali metal secondary battery, which comprises the solid electrolyte membrane of the present invention.

[0033] The battery of the present invention, except for the electrolyte membrane of the present invention, may have conventional components and assembly structures.

[0034] The alkali metal secondary battery of the present invention may be a lithium secondary battery, a sodium secondary battery or a potassium secondary battery.

[0035] The invention also discloses a method for preparing an alkali metal secondary battery, which is prepared by compounding a positive electrode, the solid electrolyte membrane and a negative electrode.

[0036] The preparation method may include the following steps: dripping the prepolymer mixed solution (precursor solution) into a smooth and flat polytetrafluoroethylene circular ring, so that the prepolymer mixed solution slowly covers the bottom of the circular ring mold, standing for 1 minute, and then irradiating with ultraviolet light for 3 minutes, and polymerizing under the action of a photoinitiator to solidify into a film, thereby obtaining a polyether-based solid electrolyte. Then, the electrolyte membrane is removed from the ring, and a button cell is assembled to perform an electrochemical performance test.

[0037] Beneficial Effects

[0038] The present invention innovatively uses photoinitiator technology to initiate the polymerization of cyclic ether monomers and crosslinkers, and through the combination of crosslinkers, auxiliary agents I and auxiliary agents II, the polymerization behavior can be optimized, and the polymerization efficiency and uniformity can be improved. This method can not only effectively control the polymerization time and degree of polymerization, but also significantly improve the ionic conductivity and electrochemical properties of the solid electrolyte. For example, the room temperature ionic conductivity of the solid electrolyte of the present invention can reach 1×10 -4 ~10 -3 S / cm, and exhibited low polarization and excellent cycle stability, which improved the performance and practical application prospects of lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is an optical photograph of the solid electrolyte membrane prepared in Example 1;

[0040] Figure 2 The impedance diagram of the solid electrolyte assembled steel symmetric battery prepared in Example 1 and Comparative Example 1;

[0041] Figure 3 The linear voltammetric scanning curves of the solid electrolyte prepared in Comparative Example 1 and Comparative Example 1 are shown;

[0042] Figure 4 The solid electrolyte assembled lithium symmetric battery cycle diagram prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0043] Embodiment 1:

[0044] In a glove box, 1,3-dioxolane (2 g, 1.88 ml) and trimethylolpropane triglycidyl ether (crosslinker, 0.06 g, 3 wt% of the monomer) were weighed into a 5 mL small glass bottle, mixed evenly, and lithium bis(trifluoromethyl)sulfonyl imide (0.574 g, 1.06 mol / L) was added, mixed and stirred to make the lithium salt completely and evenly dissolved, and then the auxiliary agent I (Formula 1-A-1; 0.02g, accounting for 1wt% of the monomer) and auxiliary II (Formula 4-A, 0.02 g, accounting for 1 wt% of the monomer), and stirring evenly to obtain a polyether-based polymer electrolyte prepolymer mixed solution.

[0045] The prepolymer mixed solution was poured into a smooth and flat polytetrafluoroethylene circular ring, so that the prepolymer mixed solution slowly covered the bottom of the circular ring mold. After standing for 1 minute, it was irradiated with ultraviolet light (385nm, 400W) for 3 minutes. Under the action of the photoinitiator, the polymerization reaction was carried out and solidified into a film to obtain a polyether-based solid electrolyte. The electrolyte membrane was then removed from the ring, and a button battery was assembled and the electrochemical performance was tested.

[0046] The room temperature conductivity of the polymer electrolyte prepared in Example 1 is 0.53 mS / cm, and the oxidation potential is 5.4 V.

[0047] Embodiment 2:

[0048] Compared with Example 1, the only difference is that the cyclic ether monomer is replaced by 1,3-dioxolane with 1,3-dioxane, the cross-linking agent is 4% of the monomer weight, the auxiliary agent I and the auxiliary agent II are both 1.5% of the monomer weight, and the other operations and parameters are the same as Example 1.

[0049] The room temperature conductivity and oxidation potential of the polymer electrolyte prepared in Example 2 are similar to those in Example 1.

[0050] Embodiment 3:

[0051] Compared with Example 1, the only difference is that the cyclic ether monomer is replaced by 1,3,5-trioxane instead of 1,3-dioxolane, the crosslinking agent is 2.5% of the monomer weight, the auxiliary agent I and the auxiliary agent II are both 0.8% of the monomer weight, and the other operations and parameters are the same as Example 1.

[0052] The room temperature conductivity and oxidation potential of the polymer electrolyte prepared in Example 3 are similar to those in Example 1.

[0053] Comparative Example 1:

[0054] Compared with Example 1, the only difference is that the auxiliary agent I is missing, and the missing part is supplemented by an equal amount of auxiliary agent II. Other operations and parameters are the same as Example 1.

[0055] The room temperature conductivity of the polymer electrolyte prepared in Comparative Example 1 is 0.12 mS / cm, and the oxidation potential is 4.7V.

[0056] Comparative Example 2:

[0057] Compared with Example 1, the only difference is that the auxiliary agent II is missing, and the missing part is supplemented by an equal amount of auxiliary agent I. Other operations and parameters are the same as Example 1.

[0058] After adding additive I, the 1,3-dioxolane molecules in the precursor solution remained stable, no polymerization reaction occurred, the precursor solution always remained in a liquid state, and there was no viscosity trend, so the polymer electrolyte membrane could not be successfully prepared.

[0059] Comparative Example 3:

[0060] Compared with Example 1, the only difference is that the epoxy-containing crosslinking agent is missing, and the other operations and parameters are the same as those in Example 1.

[0061] The room temperature conductivity of the polymer electrolyte prepared in Comparative Example 1 is 0.30 mS / cm, and the oxidation potential is 4.5 V.

[0062] test:

[0063] Impedance and ionic conductivity:

[0064] A steel symmetrical battery (the positive and negative electrodes are steel sheets, and the polymers prepared in the examples and comparative examples are electrolyte membranes) was assembled in a glove box, and an electrochemical impedance spectroscopy test was performed using a Gamry electrochemical workstation to measure the impedance of the battery. The steel symmetrical battery was then disassembled, and the thickness of the in-situ polymerized solid electrolyte membrane was measured and calculated according to the ionic conductivity formula.

[0065] Number of migrations:

[0066] A lithium symmetrical battery (the positive and negative electrodes are lithium sheets, and the polymer prepared in the examples and comparative examples is the electrolyte membrane) is assembled in a glove box. The constant voltage polarization method is used in conjunction with the AC impedance method. First, the impedance of the symmetrical battery before polarization is measured, and then a bias voltage of 10mV is set to record the response current curve over time. The response current is terminated when it reaches stability, and the impedance of the symmetrical battery after polarization is measured again. The polymer solid electrolyte is calculated according to the lithium ion transfer number formula.

[0067] Linear cyclic sweep voltammetry:

[0068] Assemble a steel-to-lithium battery (the positive electrode is a steel sheet, the negative electrode is a lithium sheet, and the polymer prepared in the example and comparative example is an electrolyte membrane). Call the linear scanning program of the electrochemical workstation, set the voltage from 3V to 6V, and the scanning rate is 1mV / s. Measure the oxidation potential of the polymer solid electrolyte. When the response current is 10μA, it is the corresponding oxidation potential.

[0069] Symmetrical battery long cycle test:

[0070] The lithium symmetric battery was assembled in a glove box and placed in a blue electric test system with a current density of 0.1 mA cm -2Cycle, single charge or discharge time is 1 hour.

[0071] Table 1 Comparison of basic properties of films prepared using different photoinitiators

[0072]

[0073] It can be seen from Table 1 that the process described in the present invention can obtain a polyether solid electrolyte with excellent performance based on a new photoinitiator method.

Claims

1. A method for preparing a cross-linked polyether-based solid electrolyte, characterized in that: The precursor solution containing an ether monomer, a cross-linking agent containing an epoxy group, an electrolyte salt, an auxiliary agent I and an auxiliary agent II is polymerized under ultraviolet light to obtain; The auxiliary agent I is a compound having a structure of formula 1 and capable of releasing free radicals under ultraviolet light; the auxiliary agent II is at least one cationic organic substance selected from diazonium salts, iodonium salts, sulfonium salts, ferrocenium salts, sulfonyloxy ketones, and triarylsiloxane ethers; The R1 is at least one of H, C1-C6 alkyl, C1-C6 alkoxy, cyano, fluorine, chlorine, bromine and iodine; The R2 is an alkyl group, a phenyl group, or is cyclically linked to the α-position C of the benzene ring to form a ring; wherein the alkyl group, the phenyl group and the ring are allowed to have substituents, and the substituents include at least one of a C1-C6 alkyl group, a C1-C6 alkoxy group, a C1-C6 alkanoyl group, a phenyl group, a hydroxyl group, a phosphoryl group, a cyano group, a fluorine atom, a chlorine atom, a bromine atom and an iodine atom.

2. The method for preparing a cross-linked polyether-based solid electrolyte according to claim 1, characterized in that: The auxiliary agent I is at least one of the compounds of formula 1-A, formula 1-B, formula 1-C, and formula 1-D; The R3 to R6 are independently H, C1 to C6 alkyl, hydroxyl or C1 to C6 alkoxy, C1 to C6 alkanoyl, phenyl, hydroxyl, phosphoryl, cyano, fluorine, chlorine, bromine or iodine; The X is O or S.

3. The method for preparing a cross-linked polyether-based solid electrolyte according to claim 1, characterized in that: The auxiliary agent II is a compound containing organic cations of formula 2 to formula 5; The R7~R 12 Alone is an aromatic group; Preferably, the anions in the auxiliary agent II include at least one of hexafluorophosphate anions, tetrafluoroborate anions, hexafluoroantimonate anions, hexafluoroarsenate anions, and trifluoromethanesulfonate anions.

4. The method for preparing a cross-linked polyether-based solid electrolyte by photoinitiation according to claim 1, characterized in that: The cross-linking agent containing epoxy groups comprises at least one of pentaerythritol glycidyl ether, trimethylolpropane triglycidyl ether, polyethylene glycol diglycidyl ether, glycerol diglycidyl ether, polypropylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, resorcinol diglycidyl ether, isocyanuric acid triglycidyl ester, glycidyl ether oxypropyl cage polyhedral silsesquioxane, and 1,3-bis(3-glycidyl ether oxypropyl)tetramethyldisiloxane.

5. The method for preparing a cross-linked polyether-based solid electrolyte by photoinitiation according to claim 1, characterized in that: The ether monomer is an unsaturated epoxy monomer; preferably a three- to six-membered cyclic ether and corresponding fluorine-substituted or carbon-chain-substituted product; Further preferably, the ether monomer includes at least one of ethylene oxide, 3,4-epoxy-1-butene, 3,3,3-trifluoropropylene oxide, tetrahydrofuran, 2-methyltetrahydrofuran, 3,3,4,4,5,5-hexafluorotetrahydropyran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 4-(trifluoromethyl)-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2,2,4,4,5,5-hexamethyl-1,3-dioxolane, 1,3,5-trioxane, 2,2-dimethoxy-4-(trifluoromethyl)-1,3-dioxane, 1,3,5-trioxane, 1,3-dioxane, and 1,4-dioxane; Preferably, the electrolyte salt comprises at least one of a conductive lithium salt, a conductive sodium salt, and a conductive potassium salt, and preferably comprises at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(oxalateborate), lithium bis(fluorooxalateborate), lithium difluorobis(oxalateborate), lithium difluorobis(oxalatephosphate), lithium difluorophosphate, lithium hexafluoroarsenate, sodium bis(trifluoromethanesulfonyl)imide, sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, sodium bis(fluorosulfonyl)imide, sodium bis(oxalateborate), sodium bis(fluorooxalateborate), sodium difluorobis(oxalatephosphate), sodium difluorophosphate, sodium hexafluoroarsenate, potassium bis((fluorosulfonyl)imide), potassium fluoroborate, potassium hexafluorophosphate, and potassium perchlorate.

6. The method for preparing a cross-linked polyether-based solid electrolyte by photoinitiation according to any one of claims 1 to 5, characterized in that: In the precursor solution, the electrolyte salt concentration is 0.1-5 mol / L, the crosslinking agent content is 0.1-25 wt%, the auxiliary agent I content is 0.01-10 wt%, and the auxiliary agent Ⅰ content is 0.01-10 wt%; Preferably, the electrolyte salt concentration is 0.5 to 2 mol / L, the crosslinking agent content is 1 to 5 wt%, the auxiliary agent I content is 0.5 to 2 wt%, and the auxiliary agent II content is 0.5 to 2 wt%.

7. The method for preparing a cross-linked polyether-based solid electrolyte by photoinitiation according to claim 1, characterized in that: The wavelength of the ultraviolet lamp is 100-420nm, and can further be 380-400nm, and the irradiation intensity is 20-200mW / cm; Preferably, the polymerization time is 1 to 30 minutes.

8. A solid electrolyte membrane, characterized in that: Obtained according to the preparation method according to any one of claims 1 to 7.

9. An alkali metal secondary battery, characterized in that: Comprising the solid electrolyte membrane according to claim 8.

10. A method for preparing an alkali metal secondary battery according to claim 9, characterized in that: The positive electrode, the solid electrolyte membrane and the negative electrode are compounded to obtain the product.

Citation Information

Patent Citations

  • Solid-state battery and preparation and application of polyether solid electrolyte of solid-state battery

    CN118099514A

  • Preparation method and application of in-situ cross-linked polyether solid electrolyte

    CN118388757A

  • Setting composition for a battery electrolyte

    CN1784806A

Cited By

  • Method for preparing solid polymer electrolyte by UV (ultraviolet) photo-initiated tandem cationic polymerization

    CN120637588A